2019
DOI: 10.1002/jcla.23073
|View full text |Cite
|
Sign up to set email alerts
|

The diagnosis values of serum STAT4 and sEng in preeclampsia

Abstract: Objective To detect the levels of signal transducer and activator of transcription 4 (STAT4) and soluble endoglin (sEng) in preeclampsia patients and analyze the diagnostic values of STAT4 and sEng in preeclampsia. Methods Fifty‐four pregnant women with preeclampsia from October 2017 to June 2018 were included in this study. Twenty‐eight matched healthy pregnant women were set as the control group. The general clinical characteristics were measured. Serum STAT4 and sEng were detected by ELISA. Correlation betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Furtherly, it suggests that inflammatory response regulation is impaired in preeclamptic women.Signal transducer and activator of transcription 4(STAT4)mediates extracellular signals of inflammatory mediators by regulate the biological behavior of immune cells [23]. A small number of studies [24][25][26][27] have reported that STAT4 expression is significantly elevated in patients with preeclampsia, which is also consistent with our study. STAT4 can act on vascular endothelial cells, causing cell dysfunction, which further causes the development of preeclampsia.…”
Section: Discussionsupporting
confidence: 91%
“…Furtherly, it suggests that inflammatory response regulation is impaired in preeclamptic women.Signal transducer and activator of transcription 4(STAT4)mediates extracellular signals of inflammatory mediators by regulate the biological behavior of immune cells [23]. A small number of studies [24][25][26][27] have reported that STAT4 expression is significantly elevated in patients with preeclampsia, which is also consistent with our study. STAT4 can act on vascular endothelial cells, causing cell dysfunction, which further causes the development of preeclampsia.…”
Section: Discussionsupporting
confidence: 91%
“…STAT4 , which encodes the signal transducer and activator of transcription 4, is a key activator of immune regulating genes and was upregulated in R3 and AI placentas compared to Controls. STAT4 mediated pathways are disrupted in preeclampsia and circulating levels are elevated in patients with preeclampsia ( 46, 47 ). This differential gene expression was only seen in the placenta if the maternal infection was active or recently resolved, suggesting a long period of time is necessary to attenuate these pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, understanding the link between LIF and the pathogenic mechanisms of preeclampsia may contribute to the development of effective treatments for preeclampsia ( 64 ). Additionally, studies have shown that elevated expression of STAT4 in the serum of preeclampsia patients could act as a diagnostic indicator for the severity of the disease ( 65 ).…”
Section: The Role Of the Stat Signaling Pathway In Pregnancy-related ...mentioning
confidence: 99%